RapeLay and the return of the sex wars in Japan. Issue 1 (2nd January 2017) - Galbraith, Patrick W.
ABSTRACT: This article considers responses to RapeLay (2006), an adult computer game that allows the player to rape virtual women. RapeLay sparked controversy when it circulated globally and this filtered back into debates in Japan, which at times explicitly retrod the ground of feminist critiques of pornography in North America from the late 1970s into the 1980s. The return of 'the sex wars' in Japan in the new millennium confronts us with a fundamental question that those battles left unresolved: is fantasy itself a problem? To put it another way, are adult computer games, which involve humans in the production and reception of virtual sex acts but not in the depicted sex acts, a problem? Is it all right to fantasize about sexual violence or, as some critics argue, does such fantasy normalize sexual violence against women? Critical and cultural approaches to sexual fantasy, play and harm in Japan are considered.